2003
DOI: 10.1034/j.1600-6143.2003.30110.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Islet Yields From Macaca Nemestrina and Marginal Human Pancreata After Two‐Layer Method Preservation and Endogenous Trypsin Inhibition

Abstract: We tested whether two-layer method (TLM) pancreas preservation and trypsin inhibition (Pefabloc) during processing allows longer preservation while retaining or improving viable islet recovery. Non-marginal primate (Macaca nemestrina) and marginal human (ischemic or preservation-injured) pancreata were processed with a research-oriented pan technique (Seattle method). Organs were processed upon arrival (∫ Pefabloc), or after TLM or University of Wisconsin solution (UW) preservation (π Pefabloc). Islet yield, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 49 publications
0
80
0
Order By: Relevance
“…However, despite continuous improvements, it is not yet possible to retrieve the entire pool of islets that are contained in a pancreas (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite continuous improvements, it is not yet possible to retrieve the entire pool of islets that are contained in a pancreas (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24] These studies have shown an improvement of islet yield due to impairment of serine proteases by these inhibitors. Here we report the potency effect of these inhibitors on endogenous proteases, bacterial neutral proteases and islet function in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of Pefabloc, Trasylol and UTI during the islet isolation process has been reported to improve islet yield, presumably by inhibiting pancreatic endogenous protease activity. [16][17][18][19][20][21][22][23][24][25][26][27][28] To confirm this, we tested the effect of these inhibitors on the activity of trypsin, chymotrypsin, elastase and switch samples. Pancreatic digestion switch samples usually consist of multiple enzymes (trypsin, chymotrypsin, elastase, thermolysin/neutral protease and collagenase).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…University of Wisconsin (UW) solution is usually used for pancreas preservation. Recent reports have shown that the two-layer method (TLM), which employs oxygenated perfluorochemical (PFC) and UW solution, is superior to simple cold storage in UW solution [55][56][57]. Matsuda et al showed caspase, JNK, and p38 activity in isolated islets after preservation of UW or TLM [58].…”
Section: Brain Death and Pancreas Preservationmentioning
confidence: 99%